Children in Conflict with the Law Rights, Research and Progressive Youth Justice - Kilkelly, Ursula; Forde, Louise; Lambert, Sharon; Swirak, Katharina (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
This book presents an original synthesis of the leading international research on children in conflict with the law, providing an evidence base for a rights-based justice system. Informed by international children's rights standards, this book presents relevant research findings in a clear, succinct and accessible manner, identifying the key evidence underpinning three rights-based themes of Prevention, Diversion and Justice, and Reintegration. This book is the first analysis to map leading inter-disciplinary research against the international children's rights framework in relation to children and the justice system. In this way, it provides a unique evidence base for the implementation of children's rights in youth justice and will support all those seeking to study, advocate or implement progressive approaches to children in conflict with the law. Ursula Kilkelly is Professor of Law in the School of Law at University College Cork,Ireland. She has researched and published extensively on international children's rights, including children in conflict with the law. Ursula is co-editor of Youth Justice, the leading journal in the field, and in 2022/2023, holds the Rotating Chair in the Enforcement of Children's Rights in Leiden University, the Netherlands. Louise Forde is Lecturer at Brunel Law School, Brunel University London, UK. She researches and writes on youth justice and children's rights and has a particular interest in translating international children's rights law into practice and children's participation. Sharon Lambert is Lecturer in the School of Applied Psychology at University College Cork, Ireland. She has significant experience of working in community-based settings with socially excluded groups. Her area of expertise is trauma Informed service design. Katharina Swirak is Lecturer in the Department of Sociology and Criminology at University College Cork, Ireland. Her research interests include amongst others young people and social harm, the intersections of criminal justice and social policy and social reintegration after prison. .
1. Introduction -- 2. Children in Conflict with the Law - the Rights Based Framework -- 3. Prevention -- 4. Diversion and Justice -- 5. Reintegration -- Conclusions. .
Keywords: Juvenile delinquents; Human rights; Corrections; Punishment; Criminology; Criminal law; Family policy; Youth Offending and Juvenile Justice; Human Rights; Prison and Punishment; Crime Control and Security; Criminal Law and Criminal Procedure Law; Children, Youth and Family Policy